DAMPAK AKSES INTERNET TERHADAP AKHLAK REMAJA DI DUSUN TEBING RUBUH DESA TEBING BATU KECAMATAN SEBAWI KABUPATEN SAMBAS TAHUN 2022 - Alfida Parhanisa; Nuraini, Parni (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
the aim of this research isto describe the use of internet access by teenagers in Tebing Rubuh Sebawi district and the positive and negative impacts of internet access. The approach used is qualitative with a type of phenomenology. Data collection uses observation, interviews and documentation. Data analysis uses data reduction, data display, and verivication. The results of the research show that almost all teenagers in Tebing Rubuh access the internet using Wi-Fi by accessing services such as WWW (word, wide, wife), gopherspace, E-commerce, and chat. The positive impact of internet access on the morals of teenagers is having the nature of sympathy and helping each other. Establishing good relationships and connecting, maintaining and strengthening friendship. Can introspect and improve attitudes. Caring and like to help parents, thereby easing the burden on parents. While the negative impacts are accessibf pornography, being cruel and sadistic, committing fraud, gambing, falsifying identity, and not having a sense of caring